2022
DOI: 10.1002/jqs.3485
|View full text |Cite
|
Sign up to set email alerts
|

Holocene wet shifts in NW European bogs: evidence for the roles of external forcing and internal feedback from a high‐resolution study of peat properties, plant macrofossils and testate amoebae

Abstract: Two conspicuous wet shifts in the peat stratigraphy of Store Mosse in southern Sweden, associated with bog‐wide changes in vegetation and degree of peat decomposition, were analysed at high resolution. The bog‐surface wetness (BSW) proxy data (organic matter bulk density, C/N ratio, plant macrofossils and testate amoebae) highlight the importance of interactions between vegetation composition, microtopography and degree of peat decomposition, and show that the bog system operated consistently during the two we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
(184 reference statements)
0
1
0
Order By: Relevance
“…This was followed by colder and drier conditions until ∼1,500 years BP, after which the climate was wet and cold (Wastegård, 2022). Reports of a wet shift in mire hydrology (Rundgren et al, 2023) and increasing vertical peat accumulation rates (Larsson et al, 2017) have been reported from this period. Wetter and more suitable periods of Holocene climatic conditions may have enhanced the mire expansion patterns observed for the SMC.…”
Section: Uncertainties In the Description Of Temporal Patterns In Mir...mentioning
confidence: 99%
“…This was followed by colder and drier conditions until ∼1,500 years BP, after which the climate was wet and cold (Wastegård, 2022). Reports of a wet shift in mire hydrology (Rundgren et al, 2023) and increasing vertical peat accumulation rates (Larsson et al, 2017) have been reported from this period. Wetter and more suitable periods of Holocene climatic conditions may have enhanced the mire expansion patterns observed for the SMC.…”
Section: Uncertainties In the Description Of Temporal Patterns In Mir...mentioning
confidence: 99%